The human brain: From the cognitive spark to the digital mind - Vega Riaño, Hugo Alexander; Hernández Gamboa, José Orlando (2025)
This interdisciplinary work explores the evolution of the human brain, its relationship with learning, and the role of neuroeducation in the current context. Through an approach that integrates neuroscience, psychology, anthropology, and education, it analyzes how the brain has evolved from its biological roots to its interaction with digital culture. One of its central themes is the “cognitive spark,” which enabled Homo sapiens to develop abstract thinking, symbolic language, and complex social cooperation. Neuroeducation is presented as a bridge between brain knowledge and pedagogy, highlighting the key roles of emotion, attention, and memory in meaningful learning. Models such as the triune brain and concepts from social and cultural neuroscience are addressed, emphasizing the importance of empathy and theory of mind in social cohesion. Language is portrayed as an essential element in cultural construction. Furthermore, the impact of the digital revolution on cognitive and educational processes is examined, advocating for a critical and ethical neuroeducation. Finally, brain plasticity is emphasized as the foundation for adaptation, diversity, and inclusion in learning. Overall, the work offers a comprehensive perspective to transform education in the digital age.